Intrusion Detection System for VANET Based on BFO Algorithm (International Journal of Advanced Research in Computer Science, 2017)
A VANET (Vehicular Ad hoc Network) is an organization-less self-forming wireless networks of routers. It has impending applications in entirely capricious and dynamic environment. In specification based Intrusion Detection system, definite physiognomies of vital objects are examined and any anomaly is noticed. We recommend a method to investigate the exposure to attacks in network, precisely the utmost communal network layer hazard, Black Hole attack and to create a specification based Intrusion Detection System (IDS) using BFO Algorithm methodology. The recommended system is developed by using BFO Algorithm, which evaluates the activities of every single node and make available facts about the attack. The performance of VANET is evaluated depending upon BFO algorithm.Â Keywords: Intrusion Detection, Black Hole Attack, BFO Algorithm.